PHYTOCHEMICAL AND ANTIOXIDANT ASSESSMENT OF ALLIUM HYPSISTUM, ALLIUM PRZEWALSKIANUM AND ALLIUM WALLICHII - Shrestha, Deepak; Singh, Dr Ajay; Sharma, Dr Nishesh; Mir, Dr M. Amin; Ashraf, Dr M. Waqar (Malaysian Journal of Science, 2024)
High altitude plants are tremendously used mostly as food and traditional medicine for their role on prevention and treatment of several diseases. Thus, this study focused on comprehensive analysis of the phyto-constituents and the antioxidant activities of three plants; .Allium hypsistum, Allium przewalskanium, and Allium wallichii. Upon analysis, the phytoconstituents such as alkaloids, terpenoids, steroidal compounds, glycosides, carbohydrates and aminoacids were identified in ethanolic, n-hexane and aqueous extracts of the plant whereas saponins and quinones were not detected at all. Other photochemicals like flavonoids, phenolic compound, and tannins were found in ethanolic and water extracts but not in the n-hexane extract. The antioxidant activities were evaluated using total phenolic content (TPC) and 2, 2-diphenyl -1-picrylhydrazyl (DPPH) radical scavenging assay. TPC was assayed by Folin-Ciocalteu reagent method. The phenolic compounds were present in all three types of extracts; however, the highest TPC was estimated only in ethanolic extract of A. hypsistum i.e. 172mgGAE/100g. Among the extracts, ethanol extract of A. hypsistum showed the highest DPPH free radical scavenging property 59.44 %RSA (radical scavenging activity) when compared to the reference molecule ascorbic acid that had 75.11 %RSA. Among selected three plants, both TPC and %RSA revealing the antioxidant activities were found to be higher in A. hypsistum followed by A. prsewalskanium and A. wallichii. Furthermore, relationship between TPC and DPPH activity (%RSA) were established and found weak to strong correlation but they were statistical non-significant. From this study, such findings may help to know chemical constituents and medicinal values of Allium species which may lead to develop new phytomedicines and use of these plants in herbal therapy.